2021
DOI: 10.1021/acsomega.1c01143
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation of Gas Hydrate Production Performance of the Depressurization and Backfilling with an In Situ Supplemental Heat Method

Abstract: The depressurization and backfilling with an in situ supplemental heat method had been proposed to enhance the gas production of methane hydrate reservoir. This novel method is evaluated by a numerical simulator based on the finite volume method in this work. Based on the typical marine low-permeability hydrate-bearing sediments (HBS), a reservoir model with gas fracturing and CaO powder injection is constructed. The simulation results show that the stimulated fractures could effectively enhance the pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In this work, the lateral heat conduction was considered a one-dimension steady heat conduction problem in each temporal interval. As a conventional simplifying method (Li G. et al, 2012;Chen et al, 2018;Yu et al, 2019;Xu et al, 2021), we assumed that the expansion of the disturbed zone approximated to an axisymmetric process in a short-term production, and thus we calculated the corresponding heat using Fourier's law of heat conduction in cylindrical coordinates:…”
Section: Principle and Methodsmentioning
confidence: 99%
“…In this work, the lateral heat conduction was considered a one-dimension steady heat conduction problem in each temporal interval. As a conventional simplifying method (Li G. et al, 2012;Chen et al, 2018;Yu et al, 2019;Xu et al, 2021), we assumed that the expansion of the disturbed zone approximated to an axisymmetric process in a short-term production, and thus we calculated the corresponding heat using Fourier's law of heat conduction in cylindrical coordinates:…”
Section: Principle and Methodsmentioning
confidence: 99%
“…It is important to apply an effective heat source and to reduce loss in the heat generation process. Electrical heating (Callarotti, 2011;Minagawa et al, 2018), an application of heat pump to collect sea water temperature (Mori et al, 2012), geothermal energy (Japan Drilling Company, 2009), and backfilling of chemical heat sources (Xu et al, 2021) have been proposed. Among those techniques, Callarotti (2011) estimated EROI of the thermal stimulation with electric heating using analytical solutions and obtained as in the range of 4-5 without considering the efficiency of power generation.…”
Section: Heat Demand and Output By Gas Production Methods Production Techniques And Theoretical And Laboratory Evaluationmentioning
confidence: 99%
“…Simultaneously, the volume of solid Ca(OH) 2 formed after the reaction increased and the number of pores increased, which not only filled the pores left by the decomposition of NGH but also improved the permeability of the reservoir. Xu et al 141 conducted a numerical simulation study on the above scheme, and the simulation results showed that fracturing combined with the CaO scheme had an obvious promoting effect on production; the cumulative gas production increased by 200%, but the cumulative water production did not change significantly.…”
Section: Jet Breakingmentioning
confidence: 99%